Biomechanical Effects of tPRK, FS-LASIK, and SMILE on the Cornea - Xin, Yue; Lopes, Bernardo T.; Wang, JunJie; Wu, Jie; Zhu, ManMan; Jiang, MuChen; Miao, YuanYuan; Lin, HuiNi; Cao, Si; Zheng, XiaoBo; Eliasy, Ashkan; Chen, ShiHao; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To evaluate the in-vivo corneal biomechanical response to three laser refractive surgeries Methods: Two hundred and twenty-seven patients submitted to tPRK, FS-LASIK or SMILE were included in this study. All cases were examined with the Corvis ST preoperatively (up to 3 months) and postoperatively at 1 month, 3 months and 6 months and the differences in the main device parameters were assessed. The three groups were matched in age, gender ratio, corneal thickness, refractive error corrections, optical zone diameter and intraocular pressure. They were also matched in the preoperative biomechanical metrics provided by the Corvis ST including SP-A1, IIR, DA and DARatio2mm. Results: The results demonstrated a significant decrease post operation in SP-A1 and significant increases in IIR, DA and DARatio2mm (p < 0.05), all of which indicated reductions in overall corneal stiffness. Inter-procedure comparisons provided evidence that the smallest overall stiffness reduction was in the tPRK group, followed by the SMILE, and then the FS-LASIK group (p < 0.05). These results remained valid after correction for the change in CCT between pre and 6 months post operation, and for the percentage tissue altered. In all three surgery groups, higher degrees of refractive correction resulted in larger overall stiffness losses based on most of the biomechanical metrics. Conclusions: The corneal biomechanical response to the three surgery procedures varied significantly. With similar corneal thickness loss, the reductions in overall corneal stiffness were highest in FS-LASIK and lowest in tPRK.